Antibacterial Activity of Phyllophorus sp. Methanol Crude Extract on Vibrio alginolyticus and Vibrio harveyi - Sapto Andriyono; Tatak Dwi Cahyono; Endang Dewi Masithah (Journal of Marine and Coastal Science, 2022)
Utilization of natural materials sourced from the sea is very promising. These natural ingredients can function as antibacterials that are useful in a number of fields. This study aims to explore the extract of sea cucumber Phylloporus sp. as an antibacterial agent for Vibrio alginoliticus and Vibrio harveyi. The diffusion method was carried out with three treatments of sea cucumber extract starting at doses of 500, 1000 and 1500 mg/L with three replications for each treatment. Positive control was antibiotic Chloramphenicol 100 mg/ml (0.01%) and negative control with dimethylsulfoxide (DMSO) 10%. The test results showed that sea cucumber extract was able to inhibit both types of bacteria, visible from the inhibition zone formed. In Vibrio alginoliticus bacteria, the average inhibition zone formed was 0.433 ± 0.0288. In bacteria, Vibrio harveyii was inhibited by sea cucumber extract with an average inhibition zone of 0.516 ± 0.104. Inhibition zone of sea cucumber extract Phylloporus sp. lower than Chloramphenicol which is a commercial antibacterial.